2007
DOI: 10.1016/j.leukres.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in the cerebrospinal fluid of a patient receiving arsenic trioxide for relapsed acute promyelocytic leukemia with CNS involvement

Abstract: We report on a 42-year-old patient whose relapse of acute promyelocytic leukaemia (APL) included meningeal infiltration. Since he had previously experienced ATRA syndrome, he received arsenic trioxide (ATO) plus intrathecal therapy with cytarabine, prednisone, and methotrexate. We measured the concentration of arsenic in his cerebrospinal fluid (CSF). Arsenic showed a peak CSF concentration of 0.008 mg/l (0.11 micromol/l) and a nadir of 0.002 mg/l (0.027 micromol/l), both representing about 14% of blood levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…Additionally, although the combination regimen significantly decreased the incidence of bone marrow relapse, the incidence of CNS relapse remains a challenge, probably because of the relatively poor entry of the drugs through the blood-brain barrier (42)(43)(44). Because CNS leukemia may be accompanied or preceded by resurgence of the PML-RAR␣ transcript level, intrathecal prophylactics should be considered in the future, with closer monitoring of this specific disease marker.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although the combination regimen significantly decreased the incidence of bone marrow relapse, the incidence of CNS relapse remains a challenge, probably because of the relatively poor entry of the drugs through the blood-brain barrier (42)(43)(44). Because CNS leukemia may be accompanied or preceded by resurgence of the PML-RAR␣ transcript level, intrathecal prophylactics should be considered in the future, with closer monitoring of this specific disease marker.…”
Section: Discussionmentioning
confidence: 99%
“…3 We first showed in an APL patient with CNS relapse that arsenic entered the cerebrospinal fluid (CSF) during oral As 2 O 3 treatment, 4 a finding later confirmed independently in another patient receiving intravenous As 2 O 3 . 5 However, the factors controlling arsenic penetration into CSF are undefined.…”
Section: Introductionmentioning
confidence: 99%
“…This result is particularly noteworthy, since a few studies in human patients treated with ATO after APL relapse within the CNS have suggested some benefit; a recent study of 45 patients who received single cycle ATO-based consolidation chemotherapy showed remission in 41 patients and only one patient who developed CNS relapse, with a median follow-up of 2.7 years (15). Conversely, others have shown that in two APL patients, when ATO levels were actually measured within the cerebrospinal fluid, ATO levels reached only 14%-18% of the serum ATO level, suggestive of relatively poor entry into the human brain (16,17). With both the Ewing sarcoma xenografts and transgenic mouse model of medulloblastoma, no clear in vivo toxicity from ATO treatment was noted at the doses tested (13).…”
Section: An Additional Mechanism For Ato Actionmentioning
confidence: 91%